GAMBARAN UMUM KECENDERUNGAN KESEHATAN MENTAL MAHASISWA - Sri Wulan Arpina; Feida Noor Laila Isti'adah; Anandha Putri Rahimsyah (Journal of Innovative Counseling : Theory, Practice, and Research, 2021)
The purpose of this study was to find out the description of the mental health continuum in UMTAS students based on gender and to plan programs to promote and improve the mental health continuum in students. This study uses a quantitative descriptive approach to reveal an overview of the mental health continuum. The research sample was UMTAS Class 2018 students, totaling 323 populations with 167 samples. The sample in this study was taken using a random sampling technique, namely by making all members of the population have the same opportunity to be sampled. The results of this study are that the general description of mental health in college students is in the flourishing continuum category with a percentage of 65%. And students who are on the moderate continuum with a percentage of 25%, while students who are on the linguistic continuum show a percentage of 10%. This illustrates the need for mental health services for students to help optimal development.